2008
DOI: 10.1523/jneurosci.4906-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Is a Novel Myelin-Associated Inhibitor to Axon Growth

Abstract: We investigated the influence of the bifunctional guidance molecule netrin-1 on axonal growth in the injured adult spinal cord. In the adult, netrin-1 is expressed on mature oligodendrocytes, cells of the central canal, and the meninges. Netrin-1 protein in white matter is selectively enriched adjacent to paranodal loops of myelin in nodes of Ranvier. The repulsion-mediating netrin-1 uncoordinated-5 (UNC5) receptors are expressed by neurons of the corticospinal and rubrospinal projections, and by intrinsic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 63 publications
2
72
0
Order By: Relevance
“…An inhibitory growth environment for axons has been attributed to products of glial cells, both oligodendrocytes and astrocytes. Myelin-derived inhibitors include Nogo-A (3, 4), myelin-associated glycoprotein (5, 6) (MAG), oligodendrocyteassociated glycoprotein (OMgp), repulsive guidance molecule (RGM) (7), semaphorins (8), and netrins (9). Activated astrocytes at the injury site proliferate to form a glial scar (10,11) and enhance the deposition of inhibitory chondroitin sulfate proteoglycans (12)(13)(14).…”
Section: Neurology | Locomotionmentioning
confidence: 99%
“…An inhibitory growth environment for axons has been attributed to products of glial cells, both oligodendrocytes and astrocytes. Myelin-derived inhibitors include Nogo-A (3, 4), myelin-associated glycoprotein (5, 6) (MAG), oligodendrocyteassociated glycoprotein (OMgp), repulsive guidance molecule (RGM) (7), semaphorins (8), and netrins (9). Activated astrocytes at the injury site proliferate to form a glial scar (10,11) and enhance the deposition of inhibitory chondroitin sulfate proteoglycans (12)(13)(14).…”
Section: Neurology | Locomotionmentioning
confidence: 99%
“…This suggests that there may be an inherent ability for certain populations of cut axons to respond to guidance cues and cross the midline. Low et al (2008) have shown that cut rubrospinal axons respond to netrin-1 after SCI. However, the study by Low et al (2008) showed that netrin-1 inhibits rubrospinal axon growth rather than guide axons across the midline.…”
Section: Crossing the Midlinementioning
confidence: 99%
“…In contrast to corticospinal axons, lesioned rubrospinal axons show a limited degree of spontaneous growth into naive fibroblast grafts placed in the lesion site ( Figure 4g, black arrowheads). 8,19 We then tested a candidate regeneration-enhancing gene, a constitutively active form of 'deleted in colorectal cancer' (DCC), in the above in vivo model of spinal cord injury. DCC is the attraction-mediating receptor for the bimodal ligand netrin-1, which is implicated in directing and accelerating axon outgrowth during CNS development.…”
Section: Expression Of a Therapeutic Gene Candidate And Fluorescent Tmentioning
confidence: 99%
“…43 The resulting DCC version, myrDCCDP1, can no longer form heteromeric complexes with the repulsion-mediating netrin-1 receptors of the Unc5 family, which are endogenously expressed in adult corticospinal and rubrospinal neurons. 19 Deletion of the P1 domain thus selectively allows myrDCCDP1 homo-complex formation. Overexpression of myrDCCDP1 has previously been shown to enhance axonal growth in vivo when overexpressed in Caenorhabditis elegans neurons.…”
Section: Expression Of a Therapeutic Gene Candidate And Fluorescent Tmentioning
confidence: 99%
See 1 more Smart Citation